Serviço Social e Forças Armadas: desafios e possibilidades no âmbito da Força Aérea Brasileira no capitalismo contemporâneo - Freitas, Analice Barreto de Moura Costa (2021)
The research of Social Work in its military condition requires examining the dilemas and tensions that permeate the Armed Forces and their relationship with society, placing the profession in the movement of correlation of social, political and institutional forces. From a theoretical-methodological point of view, we chose the perspective of totality in the analysis of social life and the object of study, considering the foundations, principles and values of the ethical-political project of Social Work. We used the documentary analysis of the professional legal sphere and its interlocution with the legal norms of military field to identify the main contradictions in the practice of social workers in the Air Force Command. In addition, through critical-dialectical reasoning and bibliographic studies, we characterize the socio-occupational space and identify the capacities and challenges of professional actions in view of working conditions, besides the advances and setbacks in the materialization of the political ethical project in this area. The main results of the research indicated the coexistence of antagonistic professional projects in dispute in the principal guideline of work in the Brazilian Air Force; although the entities category representing appropriated the profession in the military context to guarantee professional prerogatives, the institution moved towards an attempt to suppress the political dimension of social work and its return to technicality and modernization; the incompatibility of the profession’s ethical-political project with military institutional values ratifies the need for a social worker to be committed to the professional ethos in defending those who make up the majority of the demand in this space.